Social Manufacturing on Industrial Internet - Jiang, Pingyu; Xiong, Gang; Nyberg, Timo R.; Shen, Zhen; Yang, Maolin; Xiong, Guangyu (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The fast development of the industrial internet is boosting the evolution of the manufacturing industry to a new stage of socialization, servitization, universal interaction and connection, and platformization. Under this background, social manufacturing emerged as a new kind of manufacturing paradigm, established based on the self-driven, self-organizing and self-adaptive cyber-physical-social interaction among extensive numbers of socialized manufacturing resource providers. Up until now, social manufacturing has drawn attention from both academic and industrial fields due to its promising research and application values. However, social manufacturing is still at its infant stage as the fast development of the industrial internet, artificial intelligence, collective intelligence, cloud/edge/fog computing, and a new generation of information and communication technologies, etc., are changing the interaction, configuration and operation mechanisms of social manufacturing every day. In this regard, this Special Issue is established to explore precisely how the newly emerged social manufacturing paradigm influences the trends of mass customization and the configuration/operation patterns during order delivery, and exactly how the advanced information technologies can boost the development and application of social manufacturing